Studies on Coefficient Estimates and Fekete-Szegö Problem for a Class of Bi-Univalent Functions Associated With \((p,q)\)-Chebyshev Polynomial - Kavitha, D.; Dhanalakshmi, K. (Communications in Mathematics and Applications, 2021)
In this present work, authors studied and investigated the concept of \((p,q)\)-Chebyshev polynomial of second kind for the subclass of analytic bi-univalent function with respect to the subordination. We give an elementary proof to estimate the coefficient bounds for the bi-univalent functions defined in the open unit disk. Also, we included the result of Fekete-Szegö theorem.